Residents' quality of life and attitudes toward education tourism development in North Cyprus - Sarigul, Zeynep (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
Tourism has become one of the largest and fastest growing economic sector in the world. However, the development and changes of a tourism destination has a number of effects especially on people who are living there. Tourism is related with social, economic, and environmental benefits and according to this; the quality of life (QOL) of the local people has many connections with the development of tourism. The aim of this study is to investigate the influence of demographics, the areas of quality of life and residential statuses on the attitudes of the local people in North Cyprus about the development of future educational tourism. The important contribution of this study is to identify the predictive power of different dimensions of quality of life, demographic profile structure and residential status on attitudes towards the development of educational tourism in the North Cyprus. The acquisition of support from local residents is a very important area in terms of the sustainability of educational tourism and the quality of life has an important role in determining the attitude of the people. The working group consisted of 523 local people in five different regions where Northern Cyprus Universities were located. In order to measure the attitudes towards the development of future education tourism, a scale of 3 items was used, and the "Tourism and Quality of Life Scale" which consisting of 49 items and modified by Liang and Hui (2016), were used in the study. The results of this study generally have shown that the positive attitudes of local people depend on the community well-being domain of ETQOL in particular. Furthermore, the results show that the middle and high income groups have more positive attitudes than low and very high income groups towards education tourism development. In addition, homeowners and rentals have a positive attitude towards the development of educational tourism compared to those residing in the dormitories. In addition, no significant differences were found regarding age, gender, educational status, number of children and marital status. Keywords: Quality of life, education tourism, tourism development, North Cyprus, resident attitudes.

Öz: Turizm, dünyanın en büyük ve en hızlı gelişen ekonomik sektörlerden biri haline geldi. Fakat, bir turizm destinasyonunun gelişimi ve değişimi özellikle orada yaşayan insanlar üzerinde bir takım etkilere sahiptir. Turizm sosyal, ekonomik ve çevresel faydalarla ilgilidir ve buna göre yerel halkın yaşam kalitesi, turizmin gelişmesiyle birçok bağlantıya sahiptir. Bu çalışma ile demografik özelliklerin, yaşam kalitesinin alanlarının ve yerleşim durumunun Kuzey Kıbrıs’ taki yerel halkın, gelecekteki eğitim turizminin gelişmesine yönelik tutumlarındaki etkileri araştırılmaktadır. Bu çalışma ile yaşam kalitesinin farklı boyutlarının, demografik yapının ve konut durumunun, eğitim turizminin gelişmesine yönelik tutumlardaki tahmini gücünün belirlenmesi ile katkısı olacağı düşünülmektedir.. Eğitim turizminin sürdürülebilirliği açısından yerel halkın desteğinin alınması çok önemli bir boyutu teşkil etmektedir ve kişilerin sahip oldukları tutumun belirlenmesinde yaşam kalitesinin etkin bir rolü bulunmaktadır. Araştırma grubu Kuzey Kıbrıs’ taki üniversitelerin konumlandığı beş farklı bölgedeki 523 konut sakininden oluşmaktadır. Gelecekteki eğitim turizminin gelişmesine yönelik tutumların ölçülmesi amacıyla 5 puanlık ve 3 maddeden oluşan skala (Latkova & Vogt, 2012; Wang & Pfister, 2008) ile, 49 maddeden oluşan ve Liang and Hui (2016) tarafından modifiye edilen "Turizim ve Yaşam Kalitesi Ölçeği" araştırmada kullanılmıştır. Bu çalışmanın sonuçları genel olarak ortaya koyuyor ki, gelecekteki eğitim turizminin gelişmesine yönelik yerel halkın sahip olduğu olumlu tutumları özellikle yaşam kalitesinin “Toplum refahı” boyutuna bağlıdır. Bunun yanı sıra, orta/yüksek gelir grubundakiler düşük/ çok yüksek gelir grubundakilere oranla daha olumlu bir tutum sergilemektedirler. Ayrıca, yerleşim durumunun da yerel halkın tutumlarında etkili olduğu tespit edilmiştir ve buna göre, ev sahipleri ve kiracılar, lojmanda ikamet edenlere oranla eğitim turizminin gelişmesine yönelik daha olumlu bir seviyede pozitif tutum sergilemektedirler. Ayrıca, yaş, cinsiyet, eğitim durumu, medeni durum ve çocuk sayısı ile ilgili anlamlı bir farklılaşma tesbit edilmemiştir. Anahtar Kelimeler: Yaşam kalitesi, eğitim turizmi, turizmin gelişimi, Kuzey Kıbrıs Türk Cumhuriyeti, yerleşik tutumları.
Master of Science in Tourism Management. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Tourism, 2017. Supervisor: Assoc. Prof. Dr. Ali Öztüren.
Keywords: Tourism; Cyprus, North; Quality of life; education tourism; tourism development; North Cyprus; Resident Attitudes